Anne of Green Gables - West, Clare (Oxford bookworms library. Human interest, Stage 2, 2008)
Anne, an eleven-year-old orphan, is sent by mistake to live with a lonely, middle-aged brother and sister on a Prince Edward Island farm and proceeds to make an indelible impression on everyone around her.